Molecular Epidemiology of Influenza A/H3N2 Viruses Circulating in Uganda - Byarugaba, Denis K.; Ducatez, Mariette F.; Erima, Bernard; Mworozi, Edison A.; Millard, Monica; Kibuuka, Hannah; Lukwago, Luswa; Bwogi, Josephine; Kaira, Blanche B.; Mimbe, Derrick; Schnabel, David C.; Krauss, Scott; et al. (PLoS ONE, 2011)
The increasing availability of complete influenza virus genomes is deepening our understanding of influenza evolutionary dynamics and facilitating the selection of vaccine strains. However, only one complete African influenza virus sequence is available in the public domain. Here we present a complete genome analysis of 59 influenza A/H3N2 viruses isolated from humans in Uganda during the 2008 and 2009 season. Isolates were recovered from hospital-based sentinel surveillance for influenza-like illnesses and their whole genome sequenced. The viruses circulating during these two seasons clearly differed from each other phylogenetically. They showed a slow evolution away from the 2009/10 recommended vaccine strain (A/ Brisbane/10/07), instead clustering with the 2010/11 recommended vaccine strain (A/Perth/16/09) in the A/Victoria/208/09 clade, as observed in other global regions. All of the isolates carried the adamantane resistance marker S31N in the M2 gene and carried several markers of enhanced transmission; as expected, none carried any marker of neuraminidase inhibitor resistance. The hemagglutinin gene of the 2009 isolates differed from that of the 2008 isolates in antigenic sites A, B, D, and to a lesser extent, C and E indicating evidence of an early phylogenetic shift from the 2008 to 2009 viruses. The internal genes of the 2009 isolates were similar to those of one 2008 isolate, A/Uganda/MUWRP-050/2008. Another 2008 isolate had a truncated PB1-F2 protein. Whole genome sequencing can enhance surveillance of future seasonal changes in the viral genome which is crucial to ensure that selected vaccine strains are protective against the strains circulating in Eastern Africa. This data provides an important baseline for this surveillance. Overall the influenza virus activity in Uganda appears to mirror that observed in other regions of the southern hemisphere.
Keywords: Molecular Epidemiology; Influenza A/H3N2 Viruses; Uganda